Changing organisational structures in Slovenia - Marco Hocevar; Marko Jaklič; Maja Zaman (Journal for East European Management Studies, 1999)
Slovenia's post World War II economic developments from a centrally-planned economy to an integrated self-management system have resulted in a specific organisational structure that, to some extent, continues to influence current developments in the organisational field. The beginning of this article deals with changes in organisational structures of Slovenian companies in the context of the changing environment from the industrialisation to the transition period. The subsequent chapter describes the findings of the empirical research, which studied organisational changes of eight Slovene enterprises in 1996. In conclusion, possible future developments in the organisational field in Slovenia stand out. – – Sloweniens ökonomische Entwicklungen nach dem zweiten Weltkrieg, von einer zentralen Planwirtschaft hin zu einem integrierten selbst-organisierenden System, resultierten in einer spezifischen Struktur. Diese spezifische Struktur beeinflußt noch immer aktuelle Entwicklungen im Bereich der Organisation. Der Anfang dieses Artikels handelt von Veränderungen in den Organisationsstrukturen slowenischer Unternehmen. Im darauf folgenden Kapitel werden die Ergebnisse einer empirischen Studie beschrieben, welche die organisatorischen Veränderungen von acht slowenischen Unternehmen im Jahr 1996 zum Thema hat. In der Zusammenfassung werden mögliche künftige Entwicklungen hervorgehoben.
Keywords: 650